232k views
5 votes
Solve the system of equations 3x - 4y +z=39, -3x + y -2z=-30, 2x -2y + 3z=43

User Kizzy
by
4.5k points

1 Answer

1 vote

Answer:

x = 2, y = -6, and z = 9

Explanation:

This question can be solved using multiple ways. I will use the Gauss Jordan Method.

Step 1: Convert the system into the augmented matrix form:

• 3 -4 1 | 39

• -3 1 -2 | -30

• 2 -2 3 | 43

Step 2: Add row 1 it into row 2:

• 3 -4 1 | 39

• 0 -3 -1 | 9

• 2 -2 3 | 43

Step 3: Multiply row 1 with -2/3 and add it in row 3 and then multiply row 3 with 3:

• 3 -4 1 | 39

• 0 -3 -1 | 9

• 0 2 7 | 51

Step 4: Multiply row 2 with 2/3 and add it in row 3 and then multiply row 3 with 3:

• 3 -4 1 | 39

• 0 -3 -1 | 9

• 0 0 19/3 | 57

Step 5: It can be seen that when this updated augmented matrix is converted into a system, it comes out to be:

• 3x - 4y + z = 39

• -3y - z = 9

• (19/3)z = 57 (This implies that z = 9.)

Step 6: Since we have calculated z = 9, put this value in equation 2:

• -3y - 9 = 9

• -3y = 18

• y = -6.

Step 8: Put z = 9 and y = -6 in equation 1:

• 3x - 4(-6) + 9 = 39

• 3x + 24 + 9 = 39

• 3x = 6.

• x = 2.

So final answer is x = 2, y = -6, and z = 9!!!

User Rabbi Shuki Gur
by
6.1k points